Evolution of psychotherapy 2017. (Academic Video Online, 2018)
At the heart of psychotherapy is the idea that listening to someone is an inherently healing act. Can an understanding of the grammar of music help us better understand the grammar of how patients communicate? Can Mozart help transform how we listen? Join NPR and PBS commentator Rob Kapilow [or conductor/composer/author--whichever you think is better] for a unique exploration inside the language of music to see if it can help us learn to listen like Mozart. Educational Objectives: Discuss the differences between hearing and listening. Describe ways in which understanding musical narratives can provide new models for understanding patient narratives. Discuss the grammar of musical storytelling and its relationship to patient storytelling.